Suffodit inguinal: Genital attacks on Roman emperors and other primates. (2014) - Betzig, Laura
Abstract : When Julius Caesar was stabbed, 23 times, on the Ides of March, at least one of the daggers is supposed to have gone into his groin. He wasn't the last Roman to have his privates attacked. And he wasn't the last primate. In competition for sexual access, gonads are occasionally targeted: canine incisions in monkey and ape scrota are not uncommon; and rumors had a number of Roman emperors—from Caligula and Nero, to Galba, Vitellius, Domitian, Commodus, Caracalla, Elagabalus, to Balbinus, Pupienus and Valerian over the course of the third century crisis—done in with their genitals at risk, or with their genitals cut off.